Recent Innovations in Silk Biomaterials (Journal of Fiber Bioengineering and Informatics, 2010)
Silk contains a fibre forming protein, fibroin, which is biocompatible, particularly after removing the potentially immunogenic non-fibroin proteins. Silk can be engineered into a wide range of materials with diverse morphologies. Moreover, it is possible to regenerate fibroin with a desired amount of crystallinity, so that the biodegradation of silk materials can be controlled. These advantages have sparked new interest in the use of silk fibroin for biomedical applications, including tissue engineering scaffolds and carriers for sustained release of biologically active molecules. This article summarizes the current research related to the formation of silk materials with different morphologies, their biocompatibility, and examples of their biomedical applications. Recent work on the preparation of silk particles by mechanical milling and their applications in silk composite scaffolds is also discussed.